Walled-off pancreatic necrosis - Stamatakos, Michael (Baishideng, 2010)
Walled-off pancreatic necrosis (WOPN), formerly known as pancreatic abscess is a late complication of acute pancreatitis. It can be lethal, even though it is rare. This critical review provides an overview of the continually expanding knowledge about WOPN, by review of current data from references identified in Medline and PubMed, to September 2009, using key words, such as WOPN, infected pseudocyst, severe pancreatitis, pancreatic abscess, acute necrotizing pancreatitis (ANP), pancreas, inflammation and alcoholism. WOPN comprises a later and local complication of ANP, occurring more than 4 wk after the initial attack, usually following development of pseudocysts and other pancreatic fluid collections. The mortality rate associated with WOPN is generally less than that of infected pancreatic necrosis. Surgical intervention had been the mainstay of treatment for infected peripancreatic fluid collection and abscesses for decades. Increasingly, percutaneous catheter drainage and endoscopic retrograde cholangiopancreatography have been used, and encouraging results have recently been reported in the medical literature, rendering these techniques invaluable in the treatment of WOPN. Applying the recommended therapeutic strategy, which comprises early treatment with antibiotics combined with restricted surgical intervention, fewer patients with ANP undergo surgery and interventions are ideally performed later in the course of the disease, when necrosis has become well demarcated.